2019
DOI: 10.3390/cryst9110547
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Pyramid Structure Substrate Utilized for Epitaxial Growth Free-Standing GaN

Abstract: Metal-organic chemical vapor deposition (MOCVD)-grown GaN on sapphire substrate was etched by hot phosphoric acids. Pyramid structures were obtained in the N-polar face of the MOCVD-GaN. Details of the formation process and morphology of the structures were discussed. The crystallographic plane index of the pyramid facet was calculated dependent on the symmetry of the wurtzite crystal structure and the tilt angle. The substrates with pyramid structures were utilized in subsequent hydride vapor phase epitaxy (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…25 As the interaction between III-nitride and 2D insertion layer is pure vdW force, the spontaneous delamination always happens during the cooling since their thermal expansion coefficients are different, 26,27 and it accompanies with the ruining of the III-nitride membrane. 28,29 On the other hand, the pristine 2D insertion layer is absent of dangling bonds, it is difficult for the III-nitride nucleation and growth. The artificial generation of defects or impurity atom doping via pre-treatment of the 2D insertion layer is carried out to activate nucleation sites.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 As the interaction between III-nitride and 2D insertion layer is pure vdW force, the spontaneous delamination always happens during the cooling since their thermal expansion coefficients are different, 26,27 and it accompanies with the ruining of the III-nitride membrane. 28,29 On the other hand, the pristine 2D insertion layer is absent of dangling bonds, it is difficult for the III-nitride nucleation and growth. The artificial generation of defects or impurity atom doping via pre-treatment of the 2D insertion layer is carried out to activate nucleation sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zhou et al and Jia et al also demonstrated the separation of the III-nitride membrane from graphene-coated sapphire, and the metal-insulator-semiconductor junction and violet LED were fabricated. , However, there are two extreme conditions of III-nitride spontaneous delamination or separation failure according to the unsuited vdWE interfacial adhesion, making it challenging for further applications . As the interaction between III-nitride and 2D insertion layer is pure vdW force, the spontaneous delamination always happens during the cooling since their thermal expansion coefficients are different, , and it accompanies with the ruining of the III-nitride membrane. , On the other hand, the pristine 2D insertion layer is absent of dangling bonds, it is difficult for the III-nitride nucleation and growth. The artificial generation of defects or impurity atom doping via pre-treatment of the 2D insertion layer is carried out to activate nucleation sites. However, it is recognized as a destructive way to simultaneously cause the C–C bond breakage and lattice structure missing.…”
Section: Introductionmentioning
confidence: 99%